In Vitro Embryo Production in Ruminants (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book presents the latest advances in assisted reproductive technologies applied to ruminants, such as multiovulation, artificial insemination, embryo transfer, and in vitro fertilization (IVF), which have been useful tools to accelerate the genetic progress in these species. The reader will find detailed studies on bisons, bovines, and goats